Effects of Rolling Reduction and Strength of Composed Layers on Bond Strength of Pure Copper and Aluminium Alloy Clad Sheets Fabricated by Cold Roll Bonding - Yoji Miyajima; Kotaro Iguchi; Susumu Onaka; Masaharu Kato (Advances in Materials Science and Engineering)
Three types of clad sheets, Cu/Al, Cu/AA5052, and Cu/AA5083, were produced by cold roll bonding with the rolling reduction of 50% and 75%. Tensile shear tests which give tensile shear strength were performed in order to assess the bond strength. Scanning electron microscopy was performed on the fractured interface produced by the tensile shear tests, which suggests that the fracture occurs within the Al alloy layer. The tensile shear strengths considering the area fraction of deposit of Al alloy on Cu side were compared with the shear stress converting from the ultimate tensile strengths. As a result, the tensile shear strength of the clad sheets is attributed to the shear strength of Al alloy layer close to the well bonded interface. A simple model was proposed that explains the effects of the rolling reduction and area fraction of deposit of Al alloy.